Taxonomy of Leodice Lamarck, 1818 (Annelida, Eunicidae) from Northeast Brazil (Tropical Southwest Atlantic Ocean) with description of a new species - Souza, Thaís Kananda Da Silva; Zapff, Luana; Christoffersen, Martin Lindsey; Zanol, Joana (Zootaxa, 2024)
Currently, Leodice has 34 species recorded worldwide. Among these, seven species are known along the Brazilian coast. This study is based on material collected during the Marine Algae project conducted in 1981 along the Continental Shelf of the State of Paraíba, at depths of 10–35 m. In this study, we present three new records: L. pellucida comb. nov. for South America, L. marcusi for northeastern Brazil, and L. unifrons for the State of Paraiba. A new species of Leodice is described from the State of Paraiba, Northeast Brazil, Leodice ivanildae sp. nov. This taxonomic study increases the number of known species of Leodice to 37, with nine occurring in Brazil. Additionally, it expands the species of Leodice known from the State of Paraiba, Brazil, from two to six.